Indoor thermal and humid stratification and statistical distribution in ice arenas. (15th May 2023) - Lin, Wenyu; Liu, Xiaohua; Zhang, Tao
Abstract: On-site measurements in four different ice arenas were carried out under multiple working conditions to study the indoor vertical temperature and humidity distributions. It's indicated that air distribution system has a great impact on the vertical profiles and brings about different inflection points. In order to achieve the same moisture level of around 3 g/kg in the occupied ice field, supply air humidity of jet ventilation should be reduced to 0.4 g/kg while that of ground displacement ventilation could be as high as 3.0 g/kg. The vertical profiles under different air distribution systems are simplified by calculating the air parameter discrepancy brought by dehumidification air supply in the present research. The discrepancy profile was characterized by Gaussian function with three shape coefficients. Based on the measured results, the variation of shape coefficients with different influencing factors was investigated. It is demonstrated that the extreme point coefficient can be estimated by the height of the air outlet, while the scaling range coefficient varied linearly with the relative air supply parameters. This study accumulated considerable measured data to comprehensively understand the current situation of temperature and humidity stratification in ice arenas. The proposed statistical variation distribution contributes to the precise environmental control and the efficient design of ice arenas. Highlights: On-site measurement was carried out in four ice rinks with different characteristics. Ground displacement ventilation was superior in dehumidification efficiency. Vertical profiles were characterized by a generalized distribution curve. Variation of shape coefficients with different factors was investigated.